Interfacial engineering of 2H‑MoS2/N-doped carbon composite for fast potassium interfacial storage - Wang, X.; Zhang, P.; Lu, Chunsheng; Li, X.; Dou, A.; Hou, X.; Liu, Y. (2024)
The 2H-MoS2 incorporated with N-doped carbon (2H-MoS2/NC) with high discharge capacity has attracted more research focus as an anode material for K-ion batteries (PIBs). However, large longitudinal lattice deformation at 2H-MoS2/NC heterointerfaces caused by interfacial intercalation of K ions negatively impacts the structural stability, which limits its cycling performance. In this paper, interfacial engineering has been applied to optimize the structural stability of 2H-MoS2/NC. By using first-principle simulation, the evolutions of longitudinal lattice deformation, K adsorption/diffusion performance/behaviour, interfacial strength, and electronic property with the interfacial interlayer spacing have been systematically explored. The results show that with the increase of interlayer spacing from 5.0 to 7.0 Å, the lattice deformation, interfacial strength, and K adsorption kinetics first decrease sharply with interlayer spacing in the range of 5.0–6.5 Å, and then they drop minorly at 6.5–7.0 Å. The K interfacial diffusion capability can be improved due to the decreased charge accumulation at interface that leads to weakened K–S bonding with a rising interlayer spacing. Based on variation of structural stability and K storage performance, an optimal interlayer spacing of 6.75 Å is confirmed. These findings can provide a solid theoretical basis and guidance for the experimental preparation of high-performance 2H-MoS2/NC electrode materials and further cultivate new concepts for the optimal design of two-dimensional composite electrode materials. Graphical Abstract: (Figure presented.)